Optimizing the Shortest Route Problem in Pagoh Using Ant Colony Optimization Algorithm - MOHD RIPI, NUR NADHIRAH; KAMARDAN, MUHAMAD GHAZALI (Enhanced Knowledge in Sciences and Technology, 2026)
In this research, the model of the Pagoh Education Hub was made using the graph model, and the Ant Colony Optimization technique was employed for finding the shortest path problem between critical locations on the campus. With the help of the ACO technique, it was possible to find the shortest possible path from the Universiti Tun Hussein Onn Malaysia (UTHM) campus to the Politeknik Tun Syed Nasir (PTSN), going through the Education Hub Library, which measured a total distance of 1.1 km. These findings clearly state that the ACO technique can be effectively used for finding the shortest possible route, which will be reliable as well as optimized according to the shortest path on the network graph. In this regard, it has been found that the ACO technique performs much more effectively compared to the human inspection process, especially while dealing with larger networks. The results obtained clearly justify that the model developed has been accurate, as the optimized route clearly depicts the correctness of the network developed. Further, it has been found that this research clearly has implications on finding more complex routes while dealing with larger education systems or larger geographical areas. In summary, the application of the ACO algorithm offers a promising solution for shortest route problems in campus and similar real-world. environments, supporting smarter and more adaptive navigation systems.